The last raven - Jones, Helen Glynn (One More Chapter, 2024)
"As sole heir to the House of Raven, there is nothing Emelia can't have. The only problem is, she doesn't want it. But when the mysterious Kyle enters her closed-off existence, she sees a way out. As rebellion and dark forces swirl around her, Emelia has a choice to make--leave everyone she loves behind, or stay and accept her destiny"--Amazon.